Review of Rethinking Parameters - Samanta Planells (Universitat Autònoma de Barcelona, 2016)
This is a review of the book Rethinking Parameters, edited by Luis Eguren, Olga Fernández-Soriano & Amaya Mendikoetxea. 2016. Oxford: Oxford University Press.